Development of high-strength, economical self-consolidating concrete - Naik, Tarun R.; Kumar, Rakesh; Ramme, Bruce W.; Canpolat, Fethullah (ELSEVIER SCI LTD, 2012)
This paper presents information regarding development, properties, and advantages and disadvantages of using high-strength self-consolidating concrete in the construction industry. It also presents results of a study recently completed for manufacturing economical high-strength self-consolidating concrete containing high-volumes of fly ash. In this study, portland cement was replaced by Class C fly ash in the range of 35-55% by the mass of cement. The results of fresh and hardened properties of concrete show that the use of high-volumes of Class C fly ash in self-consolidating concrete reduces the requirements for superplasticizer (HRWRA) and viscosity modifying agent (VMA) compared with the normal dosage for such admixtures in self-Consolidating concrete. The results further indicate that economical self-consolidating concrete with 28-day strengths up to 62 MPa can be made using high-volumes of fly ash. Such concretes can be used for a wide range of applications from cast-in-place to precast concrete construction. Published by Elsevier Ltd.
Keywords: Admixture; Bleeding; Compressive strength; Fly ash; High-strength concrete; Self-consolidating concrete; COMPACTING CONCRETE; FLY-ASH; Construction & Building Technology; Engineering; Materials Science